Developing a creative framework on the roles and effects of product placement in Malaysia’s social media landscape - Jaafar, Fazlina; Abu Bakar, Mohd Syuhaidi; Rosli, Hafizah (College of Creative Arts, 2025)
Product placement has become a popular marketing strategy in Malaysia due to the quick rise of creator-led media on social media sites like Facebook, YouTube, Instagram, and TikTok. Research on how these placements work across many channels, how Malaysian viewers view authenticity and disclosure, and how these activities differ from more conventional placements in films and TV shows is still lacking. This concept paper suggests a qualitative, exploratory design to (i) determine the purposes of product placement in creator content; (ii) investigate its influence on engagement, perceived authenticity, brand attitudes, and purchase intention; and (iii) integrate the findings into a creative framework that makes platform-specific practices, audience responses, and ethical/disclosure considerations more understandable in the Malaysian context. In-depth interviews with marketing experts and active social media users will be subjected to thematic analysis to identify patterns that connect audience outcomes (such as trust, identification, and engagement) with integration choices (such as prominence, narrative coherence, and creator–brand alignment). A practitioner-oriented, Malaysia-specific framework that directs moral, culturally relevant, and successful placement tactics while enhancing theoretical understanding of embedded persuasion, influencer credibility, and the consequences of disclosure in multicultural digital environments is the anticipated contribution.